Effects of causal explanations and sex variables on recommendations for corrective actions following employee failure - Pence, Earl C.; Pendleton, William C.; Dobbins, Greg H.; Sgro, Joseph A. (Organizational behavior and human performance, 1982)
The current study examined the effects of different causal explanations for employee failure, sex of the evaluator, and sex of the employee evaluated upon ratings of the appropriateness of 11 supervisory actions. One hundred male and 100 female subjects were randomly assigned to evaluate four male or four female employees whose performance in a management-trainee position was described as unsatisfactory. One employee was described as failing due to lack of effort, one due to lack of ability, one due to difficulty of the task, and one due to bad luck. Subjects were asked to indicate why they felt each employee failed to rate the appropriateness of 11 corrective actions for each of the four employees. The data were analyzed as a 2 × 2 × 4 mixed factors design. Results indicate that the cause for employee failure and the sex variables influence subjects' ratings of corrective actions. Coercive actions were considered most appropriate for failure due to lack of effort. Subjects appeared to concomitantly consider the internality and stability of the causes for employee failure. Regression analyses were used to examine the appropriateness of interpreting the results within an attribution theory framework.